Pengaruh Model Pembelajaran Tipe Group Investigation Pada Materi Atmosfer Terhadap Hasil Belajar Peserta Didik - Ishmata, Alnovanda Femmy; Sya, Ahman; Kusumawati, Lia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of using the Group Investigation type cooperative learning model on the learning outcomes of class X students on atmospheric material. The method used in this research is an experiment with a research design, namely pretest-posttest control group design. Sampling was done by non probability sampling using purposive sampling technique. The samples in this study were two classes, namely the experimental class and the control class with a total of 34 students in each class. The instrument used was a multiple choice test of 20 questions and a Group Investigation Sheet (LIK) for the experimental class. The results showed that the average learning outcome of the experimental class using the Group Investigation type cooperative learning model was 83.88, while the average score in the control class was 81.76. The results of hypothesis testing in this study showed the F value of 16.174> F table 4.15 and a significance value of 0.000 <0.05, it can be concluded that H0 is rejected. This means that there is a significant influence between the independent variable (Group Investigation Model) on the dependent variable (Learning outcomes) in the research experimental class.